Implementation of electronic data interchange by MISC Haulage Services Sdn. Bhd. Port Klang / Suriawati Seman - Seman, Suriawati (1992)
Container first appeared in Malaysia in the early 1970's to cope with the domestic growth of import and export, in Malaysia. Containerisation is moving its way into the hearts of manufactures in Malaysia . The role played by container haulage encourage the multimodal industries to be more efficient in future.